Witnesses as strangers responding to “Bodily Imperatives” of the poor - Simon, DX (Nederduitse Gereformeerde Teologiese Tydskrif, 2004)
The bodies and embodiment of the poor challenge the churches’ missional ethos, which entails the modes of relating and responding to the plight of the poor. It suggests that churches should deal with the “human face” of poverty at both its material and cultural dimensions, with the levels of human dignity and human identity respectively. This requires a continuous transformation of the modes of witnesses that shift between being “for” (partial inclusion of) and “with” (embracing of) the poor. “Bodily Imperatives” and agency of the poor should mainly inform and shape this process of transforming the modes and persons whenever witnesses and the poor encounter each other on the “frontier” of poverty and class. “Bodily Imperatives” of the poor echoes a call for both missional and moral responses in the process.